ROC-1, P21 and CAIX as markers of tumor aggressiveness in bladder carcinoma in Egyptian patients - Al-Sharaky, Dalia Rifaat (Diagn Pathol, 2020)
BACKGROUND: Bladder cancer (BC) is one of the most common malignancies in Egypt, representing about 8.7% of cancers in both sexes with more predominance in males, making identification of valuable predictive and prognostic markers, mandatory. Cullin-RING ligases (CRL) play an important role in the ubiquitination of cell cycle-related proteins or other proteins (e.g., DNA replication protein, signal transduction protein). Regulator of Cullins-1 (ROC-1) is a key subunit of CRL. P21 belongs to the family of cyclin dependent kinase inhibitors (CKIs) which regulates cell cycle by inactivating Cyclin- Dependent Kinases key regulators of the cell cycle. CAIX a highly active member of the family of carbonic anhydrases has gained much interest as a hypoxic marker. Hypoxia is a consequence of the rapid growth of many tumors, including bladder cancer, and is an important regulator of gene expression and resistance to chemotherapy and radiotherapy. Therefore the purpose of this study is to evaluate the role of ROC-1, CAIX and P21 and its relationship with the clinico-pathological features of bladder cancer in Egyptian patients. METHODS: Using the standard immunohistochemical technique, ROC-1, CAIX and P21 expression in 80 primary bladder carcinomas and 15 normal bladder specimens as control group were assessed. The bladder carcinoma cases included 50 cases with muscle invasive bladder cancer and 30 cases with non-muscle invasive bladder cancer. RESULTS: Over expression of ROC-1, CAIX and P21 in BC were significantly associated with muscularis propria invasion and high grade BC. ROC-1, CAIX and P21, showed significant inverse relationship in primary BC cases. CAIX expression was significantly higher in BC compared with controls. Regarding the survival analysis, expression of ROC-1, CAIX and P21 didn’t affect the survival of BC patients. CONCLUSIONS: High expression of ROC-1, CAIX and P21 could be promising potential biomarkers for identifying patients with poor prognostic factors in bladder cancer serving as potential targets for cancer therapy.